Comparison of students' foodservice satisfaction between Korea and US - Jeong, Eunkyung (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2013)
This study analyzes important factors of foodservice in school through comparison of students' satisfaction of using foodservice in Korea and US in order to meet students' expectations. The survey was composed of 4 categories including menu, service, hygiene, and facility and it was carried out in both countries to evaluate satisfaction. First, comparison of satisfaction between two countries was made using t-test. Secondly, multiple regression was performed to identify factors affecting satisfaction. As a result Korean students were more satisfied than American students in all aspects. However, regardless of nationality, the top three factors affecting the students' satisfaction were the same. The predictors were food taste (Korean 0.375 and American 0.350), menu variety (Korean 0.305 and American 0.278), and service line (Korean 0.226 and American 0.192). Despite the similarity of the predicators, it can be concluded that the difference in satisfaction level between the two nationscan be explained by the approaches to create comfortable and acceptable changes in schools' foodservice. Korea has been increasing the foodservice quality based on their objectives to provide students comfortable and positive environment when eating nutritious meals. However, US have made their main objectives on making changes to decrease youth obesity. Foodservice improvements according to continuous evaluations and surveys are necessary in order to increase students' satisfaction.